Empowering workers for retirement: challenges for industrial a social workers (2015)
Some retirees are frustrated through undue delay, and sometimes denial of gratuity and pension allowances. Preretirement stage of retirement in some cases is accompanied by some psycho-social problems like; anxiety over time management; total dependence on present salary, securing alternative residence, ignorance of what to do with pension, attitude of friends and family. Workers in this category retire into a state of confusion psychological problems, delusion and subsequently death. Many retirees easily get incapacitated while some encounter untimely death in the process. However these problems would have been minimal, if Industrial Social Workers had been employed by both government and private organizations to help the employees to prepare adequately for retirement. It was recommended that, industrial social workers should endeavour to make workers prepare well for their eventual retirement through counselling, dissemination of information as to how retirees should be mindful of their style of life. Furthermore, industrial social workers should ensure that, workplace policy makers put in place post-retirement packages that are capable of making lives of retirees comfortable and longer. Industrial social workers should ensure that, adequate social supports from friends and family members are given to the retirees.